Drivers of Natural Variation in Water-Use Efficiency Under Fluctuating Light Are Promising Targets for Improvement in Sorghum - Pignon, Charles P.; Leakey, Andrew D. B.; Long, Stephen P.; Kromdijk, Johannes (Frontiers in Plant Science, 2021)
Improving leaf intrinsic water-use efficiency ([i]iWUE[/i]), the ratio of photosynthetic CO2 assimilation ([i]A[/i]) to stomatal conductance ([i]gs[/i]), could decrease freshwater use during crop production. [i]A[/i], [i]gs[/i] and [i]iWUE[/i] are typically measured at steady-state. However, light in crop stands rapidly fluctuates, such that much of overall leaf gas-exchange occurs under non-steady-state conditions. In particular, [i]A[/i] responds more rapidly than [i]gs[/i] to changes in light, resulting in desynchronization and loss of [i]iWUE[/i] relative to steady-state. Traits have been targeted to improve [i]iWUE[/i] under fluctuating light, such as faster stomatal movement to better synchronize [i]gs[/i] with [i]A[/i], and significant diversity in these traits has been discovered in C3 species. However, within-species diversity in non-steady-state traits is poorly described in C4 crops. Additionally, while modification of [i]A[/i] or [i]gs[/i] traits independent of one another will theoretically have a proportionate effect on [i]iWUE[/i], in reality these traits are inter-dependent. It is unclear how interactions between these traits affect natural diversity in [i]iWUE[/i], and whether some traits are more tractable drivers to improve [i]iWUE[/i]. To address these knowledge gaps, measurements of steady-state and non-steady-state gas-exchange as well as stomatal patterning were obtained in 18 accessions of the C4 crop sorghum. We found significant diversity in [i]A[/i], [i]gs[/i] and [i]iWUE[/i]. Some features, such as gradual responses of [i]A[/i] to decreases in light, appeared promising for improvement of [i]iWUE[/i]. Other traits showed tradeoffs that negated benefits to [i]iWUE[/i], e.g. accessions with faster [i]gs[/i] responses to decreases in light, expected to benefit [i]iWUE[/i], also displayed more abrupt losses in [i]A[/i], resulting in overall lower [i]iWUE[/i]. Genetic engineering might be needed to break these natural tradeoffs and achieve optimal trait combinations, e.g. leaves with fewer, smaller stomata, more sensitive to changes in [i]A[/i]. We show that steady-state and non-steady-state [i]iWUE[/i] traits are important contributors to overall [i]iWUE[/i] under fluctuating light. This work was supported by the Bill & Melinda Gates Foundation, Grant Number INV-006866